2004
DOI: 10.1097/01.brs.0000129100.59913.ea
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Incidence and Risk Factors of Dysphagia in Spine Surgery Patients

Abstract: Dysphagia is a common occurrence after AC procedures but was also found after PC procedures. Intubation alone was not a risk factor for postoperative dysphagia in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
175
13
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(198 citation statements)
references
References 20 publications
7
175
13
3
Order By: Relevance
“…In all our cases, dysphagia was transient and required no special treatment. Although most studies reported that dysphagia decreases with time, the prevalence of chronic dysphagia is more common than previously considered (73,(78)(79)(80).…”
Section: Dysphagiamentioning
confidence: 64%
“…In all our cases, dysphagia was transient and required no special treatment. Although most studies reported that dysphagia decreases with time, the prevalence of chronic dysphagia is more common than previously considered (73,(78)(79)(80).…”
Section: Dysphagiamentioning
confidence: 64%
“…The severity and potential life-threatening nature of these complications from anterior cervical spinal surgery have prompted more thorough evaluations of their incidence and associated risk factors. 3,6,9,11,13,19,24,[27][28][29]33 The reported rates of dysphagia after anterior cervical surgery have varied widely, from 1% to 79%. 9 In a prospective study, Lee et al 19 found the prevalence of postoperative dysphagia at 1, 2, 6, 12, and 24 months to be 54%, 34%, 19%, 15%, and 14%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…59 Rates of dysphagia after anterior cervical surgery may be as high as 60% immediately after surgery and persist in up to 21% of patients at 6 months. 10,56,62,67,68 In addition, rates of dysphagia may be underreported in up to 80% of patients. 23 The consequences of dysphagia are greater than a need for a nasogastric or gastrotomy tube because aspiration pneumonia may develop in patients with an aberrant swallowing mechanism.…”
Section: Discussionmentioning
confidence: 99%